Code Mixing and Switching Performed by Teachers in Efl Classroom - Novi Indriyani (KOLONI, 2023)
This paper systematically aims to determine the usage of code-mixing and code-switching as the communicative strategy employed by EFL teachers. Discovering the existing types of both codes and the affected teachers’ factor of using both explicitly became the concern of this research. Thus, in-depth interviews and non-participant observation were occupied to complete the answer to this qualitative research. The findings draw that intra-sentential and inter-sentential fall as the type of code-mixing, and inter-sentential, lexical, and phonological have remained as the depicted types of code-mixing. Other findings also mentioned that upbringing factors fall into three categories: translating the words or phrases, repeating the comprehension, and simplifying certain expressions. The significance of this research is to frame up the existing phenomena of language variety in language teaching and the motives that can enhance teachers’ understanding of using both codes as communication strategies in teaching language.  Keywords: Code Mixing, Code Switching, EFL Teacher